2021
DOI: 10.3389/fspor.2021.660291
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise Cold Water Immersion Effects on Physiological Adaptations to Resistance Training and the Underlying Mechanisms in Skeletal Muscle: A Narrative Review

Abstract: Post-exercise cold-water immersion (CWI) is a popular recovery modality aimed at minimizing fatigue and hastening recovery following exercise. In this regard, CWI has been shown to be beneficial for accelerating post-exercise recovery of various parameters including muscle strength, muscle soreness, inflammation, muscle damage, and perceptions of fatigue. Improved recovery following an exercise session facilitated by CWI is thought to enhance the quality and training load of subsequent training sessions, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 131 publications
(302 reference statements)
0
24
0
Order By: Relevance
“…We have spoken previously of the importance for context when applying such results in professional practice, particularly where the athlete, environment, situation, training, and competition cycle can vary considerably [41,42]. Readers are directed to several reviews assessing this paradox [42,74,75]. Sixty-nine percent of respondents disagreed that CWI enhanced strength adaptation, showing good agreement with the scientific literature.…”
Section: Current Knowledge Of Benefits and Associated Physiological Mechanismsmentioning
confidence: 93%
“…We have spoken previously of the importance for context when applying such results in professional practice, particularly where the athlete, environment, situation, training, and competition cycle can vary considerably [41,42]. Readers are directed to several reviews assessing this paradox [42,74,75]. Sixty-nine percent of respondents disagreed that CWI enhanced strength adaptation, showing good agreement with the scientific literature.…”
Section: Current Knowledge Of Benefits and Associated Physiological Mechanismsmentioning
confidence: 93%
“…Indeed, regular CWI has been shown to attenuate the magnitude of anabolic signaling (Roberts et al, 2015) and protein synthesis (Fuchs et al, 2020), leading to reduced magnitude of strength and muscle mass gain following resistance training (Frohlich et al, 2014;Roberts et al, 2015;Fyfe et al, 2019;Poppendieck et al, 2020). Readers are directed to excellent reviews elsewhere (Broatch et al, 2018;Malta et al, 2021) and within this research topic (Petersen and Fyfe, 2021) elaborating on the mechanisms surrounding CWI and resistance training.…”
Section: Effect Of Cwi On Endurance and Resistance Exercise Adaptations: Divergent Effects Or Coordinated Regulation?mentioning
confidence: 99%
“…A recent metaanalytical review showed that CWI effects on exercise adaptations are mode-dependant, where resistance training adaptations were diminished, whilst aerobic exercise performance seemed unaffected (Malta et al, 2021). Alongside these publications, detailed narrative reviews on the adaptative response following regular CWI have been published within this research topic series (Petersen and Fyfe, 2021), and elsewhere (Broatch et al, 2018). Additionally, editorials, point-counterpoints, and opinion pieces (Allan and Mawhinney, 2017;McPhee and Lightfoot, 2017;Méline et al, 2017;Peake, 2017Peake, , 2020White and Caterini, 2017;Cheng, 2018;Ihsan et al, 2020a) have been published discussing the suitability of CWI as a post-exercise recovery tool given its dampening effect on hypertrophy gains.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists where a singular temperature-based strategy applied locally to the quadriceps over the entire recovery continuum failed to further accelerate recovery beyond the acute period (0-72 h), albeit , following severe marathon running–derived mechanical and metabolic stress (Kwiecien et al, 2020a , b ). Moreover, Petersen and Fyfe ( 2021 ) suggested, from a chronic perspective, long-term application of a singular intervention may have disadvantages relating to adaptation (Petersen and Fyfe, 2021 ). It appears that a binary perspective to recovery has arisen within the literature, which in turn may have influenced the applied setting.…”
Section: Matching the Stress And Intervention: Monitoring-based Practicementioning
confidence: 99%